The Role of Professional Identity in Mediating the Influence of Teaching Enthusiasm on Teaching Creativity - Salma Rahmadhani Puspita Sari; Muhammad Fahmi Johan Syah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Creativity plays a crucial role in solving problems through innovation, which enhances self-development, decision-making, and problem-solving abilities. In the field of education, teaching creativity enables teachers to design diverse and engaging learning experiences that cater to different student needs and learning styles. However, the effectiveness of teaching creativity is influenced by various factors, including teaching enthusiasm and professional identity. This study aims to investigate the mediating role of professional identity in the relationship between teaching enthusiasm and teaching creativity. Using a quantitative research design, data were collected from 170 pre-service teachers through questionnaires measuring Teaching Enthusiasm (TE), Professional Identity (PI), and Teaching Creativity (TC). Path Analysis was employed to examine the direct and mediating effects of professional identity. The findings indicate that professional identity plays a full mediating role between teaching enthusiasm and teaching creativity. While teaching enthusiasm alone does not significantly impact teaching creativity, the presence of a strong professional identity enhances this relationship. Teachers with high enthusiasm and a well-established professional identity are more likely to implement creative teaching methods, fostering an engaging and effective learning environment. This study underscores the importance of strengthening professional identity to optimize the benefits of teaching enthusiasm in fostering creativity. Educational institutions should implement continuous training and professional development programs to enhance teachers' professional identity, ultimately improving student learning outcomes. Future research could explore additional factors that contribute to teaching creativity, such as institutional support and teaching experience.